Penerapan Kegiatan Literasi dengan Metode Reading Aloud untuk Meningkatkan Keterampilan Membaca Permulaan Siswa Kelas Rendah (Studi Kasus pada Kelas I SDN Cinangka 03 Kabupaten Bandung) - Jenisa Tasya Kamila; Agil Nanggala (Departement of Mathematics Education, 2023)
This research was conducted to provide a description and description of beginning reading using the Reading aloud method as a way to improve and strengthen students' reading skills. The approach taken for this research is to use a qualitative approach with case studies. Methods of data collection based on the results of interviews, observations, field notes, and documentation. The data analysis technique for this research is data reduction, data presentation, and drawing conclusions. The results of this study will show how students' ability to read begins so that later it can be concluded that from cultivating reading the reading aloud method can have an influence on the reading skills of grade 1 (one) students at SDN Cinangka 03. Students' enthusiasm in learning to read with this method quite well, students' reading skills improve, and students get new vocabulary in different books